PERBAIKAN SISTEM PEMANASAN DENGAN MEMODIFIKASI TUNGKU PEMANAS YANG DILENGKAPI DENGAN CEROBONG ASAP - Kusumayanti, Heny; Astuti, Widi; Broto, R.TD Wisnu (METANA, 2011)
Abtract   The empowerment of micro industries, in emping‘s chip micro industry to the member of group which is enterprise Batang speciallized is give suitable solution to consument for giving natural culinary with high nutrition value independently and cheap. The development of micro industries is a circular activity that consist of briefing about the usage of furnace completely by stack gas as pilot plan, assitancy when the producer makes sweet emping’s chip system more delicious and better performance than product’s previous   Key word: micro industries emping’s chip.